THE INTERCONNECTION OF THE RULE OF LAW, EUROPEAN CONVENTION ON HUMAN RIGHTS PRINCIPLE OF LEGALITY, AND ARTICLE 7 OF THE ECHR (EU and comparative law issues and challenges series (ECLIC), 2024)
This paper will focus on the intricate interplay, the link between the rule of law, the principle of legality in a broader sense, and the principle of legality in a narrower sense (stricto sensu) contained in Article 7 (no punishment without the law, or nullum crimen, nulla poena sine lege) of the European Convention on Human Rights (ECHR), particularly its elements of foreseeability and accessibility. These three pillars collectively shape legal systems, ensuring justice, protecting human rights, and preventing the arbitrary exercise of power. This study's guiding concept and historical anchor is the rule of law and its connection to the principle of legality. Through a legal and historical analysis, the research seeks to define the core principles of the rule of law and trace its historical trajectory. Understanding the historical context illuminates how the rule of law has evolved, leading to the establishment of transparent, fair, and accountable legal systems. The research investigates how the ECtHR interprets and implements the principle of legality, focusing on accessibility and foreseeability, and the place and role of the judicial safeguards in connection to these two elements of legality. The authors seek to comprehend the ECtHR's scope and interpretation of these principles. In addition to legal analysis, the research incorporates a qualitative approach by reviewing relevant ECtHR case law on Article 7 ECHR and assessing its scope and impact. Therefore, the study applies the legal-historical and qualitative statistical methods, focusing on case studies of specific ECtHR cases that are significant in light of legalities in the broader sense and stricto sensu (Article 7).